If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -2w = 0 Reorder the terms: -2w + 3y = 0 Solving -2w + 3y = 0 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3y' to each side of the equation. -2w + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 -2w + 0 = 0 + -3y -2w = 0 + -3y Remove the zero: -2w = -3y Divide each side by '-2'. w = 1.5y Simplifying w = 1.5y
| 8m-160=6m+180 | | 5x+2(2x+1)=11 | | -3=3d-7d | | 6q+6q-13+4q-15=180 | | -60-5x=3x+28 | | 4z-5z+7= | | 10x+27=x+90 | | 483/540 | | -3x-2(5x-7)=-17 | | 2y+6-y=6 | | -12(v+3)=-54-9v | | 55+50+b=180 | | 5(x-6)+3=18-(3+2x) | | P=3W+10L | | I-3t=99 | | 2(x-5)-45=17-7x | | 7x-65/4=2x | | Ln(2x-1)-ln(x-1)=2 | | -9+3x=6x+18 | | 5(3x*2)= | | 106+p+9+p+19=180 | | 1/2(3.14)(5^2) | | -5(2x-3)+3x-5=-4 | | 55+66+u-38=180 | | 3x-16=x-6 | | 5(2a+4)=170 | | g+c=12-4 | | c-30+2c+c-30=180 | | -3x+1+7x=-11 | | 7(8x-7)=4(-9x+3) | | 2x-6+4x-3= | | 3x-68=-6x+31 |